A 3D coupled thermo-visco-elastic shear-lag formulation for the prediction of residual stresses in photovoltaic modules after lamination. (1st December 2016) - Ojo, S.O.; Paggi, M.
Abstract: Evaluation of the residual stress distribution arising from lamination of photovoltaic (PV) modules is important to address thermomechanically induced failure of PV modules during service. In view of the fact that PV modules contain several Silicon cells, modelling the thermo-mechanical response of PV laminates during cooling after lamination is computationally challenging. Due to the coupling between the thermal and the mechanical fields, the stress state experienced by each silicon cell in a module varies from one position to another. Here, a novel 3D coupled thermo-visco-elastic shear-lag model is proposed to determine the stress distribution in a PV module after lamination. To enhance the prediction of stress distribution in the laminate, viscoelastic properties of the EVA encapsulant are taken into account by using an asymptotic model which is stable for small and large time steps of strain increments. The results for a simulated mini-module show that residual stresses vary significantly from point to point inside the PV module.